Protocol for a single-centre, parallel-group, randomised, controlled, superiority trial on the effects of time-restricted eating on body weight, behaviour and metabolism in individuals at high risk of type 2 diabetes: the REStricted Eating Time (RESET) study - Marit E Jørgensen; Graham Finlayson; Dorte Vistisen; Jonas S Quist; Marie M Jensen; Kim K B Clemmensen; Hanne Pedersen; Natasja Bjerre; Joachim Størling; Martin B Blond; Nicolai J Wewer Albrechtsen; Jens J Holst; et al. (BMJ Open)
Introduction The aim of this study is to investigate the effects of time-restricted eating (TRE) on change in body weight and describe changes in behaviour and metabolism in individuals at high risk of type 2 diabetes.Methods and analysis The REStricted Eating Time (RESET) study is a randomised controlled parallel-group open-label trial. 100 women and men with (1) overweight (body mass index (BMI)≥25 kg/m2) and prediabetes (glycated haemoglobin 39–47 mmol/mol); or (2) obesity (BMI≥30 kg/m2) will be randomised to a control group (habitual living) or TRE (self-selected 10-hours eating window within the period from 06:00 to 20:00 in a 1:1 ratio. Testing is scheduled at baseline and after 6 weeks (mid-intervention), 3 months (post-intervention) and 6 months (follow-up). The primary outcome is change in body weight after 3 months of intervention. Secondary outcomes include changes in body composition; measures of glucose metabolism including glycaemic variability, hormones and metabolites; subjective and metabolic markers of appetite, food preferences and reward; dietary intake; physical activity, sleep, chronotype; gastric emptying, gastrointestinal transit time and motility; respiratory and glycolytic capacities; the plasma proteome and metabolome; blood pressure, resting heart rate and heart rate variability; and resting energy expenditure and substrate oxidation. Motivation and feasibility will be examined based on interviews at baseline and after 3 months. After the 3-month intervention, a 3-month follow-up period and subsequent testing are scheduled to assess maintenance and longer-term effects.Ethics and dissemination The study has been approved by the Ethics Committee of the Capital Region of Denmark (H-18059188) and the Danish Data Protection Agency. The study will be conducted in accordance with the Declaration of Helsinki. Results from the study will address whether TRE is effective and feasible in improving health outcomes in individuals at risk of lifestyle-related diseases and can potentially inform the design of feasible health recommendations.Trial registration number NCT03854656.